Prospective Pilot Study of Cyclophosphamide as an Adjunct Treatment in Patients With Adult-Onset Immunodeficiency Associated With Anti-interferon-γ Autoantibodies - Laisuan, Wannada (Open Forum Infect Dis, 2020)
BACKGROUND: Adult-onset immunodeficiency associated with interferon-γ autoantibody (IGA) is an emerging disease. The majority of patients require both antimicrobial and immunosuppressive treatments. However, anti-CD20 therapy is not fully accessible in a resource-limited setting to date. BACKGROUND: The objectives of this work were to study the efficacy of cyclophosphamide treatment and the role of laboratory biomarkers for disease progression monitoring. METHODS: A prospective pilot cohort study was conducted among patients with anti-interferon-γ autoantibodies (IGA) who had recurrent infections and required long-term antimicrobial therapy between 2015 and 2018. The patients were categorized into 2 groups: receipt of intravenous cyclophosphamide (IVCY) and receipt of anti-CD20 therapy (RTX). Clinical and laboratory data were determined. RESULTS: A total of 17 IGA patients were enrolled. Prolonged fever was the most common manifestation, and the most common infection identified was nontuberculous mycobacterial infections. Both were found in 88.24% of all patients. After completion of IVCY, 9/11 patients achieved complete remission and tended to reach remission faster compared with individuals in the RTX group. The median duration from treatment initiation to remission (interquartile range) was 84 (42–154) days in the IVCY group and 99 (51–202) days in the RTX group. In remission patients, the biomarkers of interest had normalized after treatment, except interferon γ autoantibody titers. There were no differences in adverse events among the 2 groups. CONCLUSION: IVCY may be considered as alternative therapy in this population, especially in resource-limited countries. A comparable clinical outcome to RTX may support its use on a larger scale. However, further study is encouraged.